Revisiting the Iberian honey bee (Apis mellifera iberiensis) contact zone: maternal and genome-wide nuclear variations provide support for secondary contact from historical refugia - Chávez-Galarza, Julio (2016)
Dissecting diversity patterns of organisms endemic to Iberia has been truly challenging for a variety of taxa, and the Iberian honey bee is no exception. Surveys of genetic variation in the Iberian honey bee are among the most extensive for any honey bee subspecies. From these, differential and complex patterns of diversity have emerged, which have yet to be fully resolved. Here, we used a genome-wide data set of 309 neutrally tested single nucleotide polymorphisms (SNPs), scattered across the 16 honey bee chromosomes, which were genotyped in 711 haploid males. These SNPs were analysed along with an intergenic locus of the mtDNA, to reveal historical patterns of population structure across the entire range of the Iberian honey bee. Overall, patterns of population structure inferred from nuclear loci by multiple clustering approaches and geographic cline analysis were consistent with two major clusters forming a well-defined cline that bisects Iberia along a northeastern-southwestern axis, a pattern that remarkably parallels that of the mtDNA. While a mechanism of primary intergradation or isolation by distance could explain the observed clinal variation, our results are more consistent with an alternative model of secondary contact between divergent populations previously isolated in glacial refugia, as proposed for a growing list of other Iberian taxa. Despite current intense honey bee management, human-mediated processes have seemingly played a minor role in shaping Iberian honey bee genetic structure. This study highlights the complexity of the Iberian honey bee patterns and reinforces the importance of Iberia as a reservoir of Apis mellifera diversity.